The effect of the transtheoretical model-based healthy youth program on sexual health knowledge and behavior of college women - ERGÜN, AYŞE; EROL, SAİME (My University, 2023)
College women are at more risk in terms of sexual behavior than male students. This study was carried out to determine the effect of the transtheoretical model-based Healthy Youth Program on college women\"s sexual health knowledge and behaviors. The sample of the study, which was conducted with a one-group pretest-posttest quasi-experimental design, consisted of 207 first-year college women. It was determined that the Healthy Youth Program was effective in improving the sexual health knowledge and behaviors of college women. It can be used as a guide in sexual health education in colleges.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities; Sexual health; comprehensive sexual health education; college women; transtheoretical model; STUDENTS; EDUCATION; ADOLESCENTS; UNIVERSITY; IMPACT; HIV